THE EFFECT OF MARITAL COUNSELING ON SEXUAL SATISFACTION OF COUPLES, SHIRAZ, 1380. - Mooshkbid- Haghighi; Shams- Mofarahe, Z; Majd- Timory, M.M.V; Hosseini, F (Iran University of Medical Sciences, 2002)
Background: Half of the unsuccessful marriages is due to unsatisfying sexual relation. Absence of safe sexual relation between couples leads to marital failure and repel. Accompany with other conditions such as lack of mutual understanding, the destruction of family, structure will occur, and the rate of divorce will be increased. Through marital counseling, couples information about desirable sex relation can be improved and family solidity and health will be guaranteed. Objective: To determine the effect of marital counseling on sexual satisfaction of couples. Design: This was a field trial study with control group. Sample: 60 couples were selected and randomly assigned to one of trial or control group(30 couples in counseling group and 30 in the other one). Result: Findings showed that at the beginning of the study 50% of women in counseling group had middle and 3.34% had little sexual satisfaction, 66.67% of women without counseling had high sexual satisfaction, while 60% of men in counseling group and 66.67% of them in the group without counseling, mentioned high sexual satisfaction. Meanwhile, at the beginning of the research women and men of both groups were the same from the point of sexual satisfaction, but one month later, 100% of men and women in counseling group verbalized high sexual satisfaction. Statistical tests showed that sexual satisfaction of men and women in counseling group was more than the control group. Conclusion: Findings indicated that marital counseling had a positive effect on the quality of sexual relation, and increased couples sexual satisfaction. Therefore, it is recommended that girls and boys participate in counseling sessions before marriage. Further researches in different aspects of sexual satisfaction is also recommended.